Precision distribution of fire command system based on an air-to-surface laser-guided weapons - LIANG Jiaqi, LIU Xingyu, LI Shucheng, BAI Jing, ZHANG Jiawei (Zhihui kongzhi yu fangzhen)
As an important part of the weapon system, the fire control system is the key to whether the weapon can destroy the target when performing the combat mission. The precise distribution of each subsystem of fire control is the premise of fire control system design. Based on the air-to-surface laser-guided weapons, this paper analyzes the composition and error causes of the airborne fire control system, and analyzes, calculates and models the key parameters from the two aspects of the probability of interception of the middle guidance and the probability of the hit of the terminal guidance according to the General Requirements for Error Analysis of the Fire Control System of Airborne Weapons of HB 6518. At the same time, the Monte Carlo method is used to simulate the model. The experimental results show that the model models the tactical indicators of low-speed targets with a CEP of 2 m, a long-range attack distance of 10 km, and a ground attack of less than 10 m/s.